A leucine-to-proline mutation in the putative first transmembrane domain of the 22-kDa peripheral myelin protein in the trembler-J mouse. - Suter, U (1992)
Peripheral myelin protein PMP-22 is a potential growth-regulating myelin protein that is expressed by Schwann cells and predominantly localized in compact peripheral myelin. A point mutation in the Pmp-22 gene of inbred trembler (Tr) mice was identified and proposed to be responsible for the Tr phenotype, which is characterized by paralysis of the limbs as well as tremors and transient seizures. In support of this hypothesis, we now report the fine mapping of the Pmp-22 gene to the immediate vicinity of the Tr locus on mouse chromosome 11. Furthermore, we have found a second point mutation in the Pmp-22 gene of trembler-J (TrJ) mice, which results in the substitution of a leucine residue by a proline residue in the putative first transmembrane region of the PMP-22 polypeptide. Tr and TrJ were previously mapped genetically as possible allelic mutations giving rise to similar, but not identical, phenotypes. This finding is consistent with the discovery of two different mutations in physicochemically similar domains of the PMP-22 protein. Our results strengthen the hypothesis that mutations in the Pmp-22 gene can lead to heterogeneous forms of peripheral neuropathies and offer clues toward possible explanations for the dominant inheritance of these disorders.